Study on how topography and density heterogeneities interact with the lithosphere in order to produce the observable lithospheric deformation - Shrivastava, Mahesh N. (Indian Institute of Geomagnetism, Mumbai, 2013)
In this thesis, it was investigated how topography and density heterogeneities interact with the lithosphere in order to produce the observable lithospheric deformation. This is obtained from a global CRUST2.0 model providing the elevation and lateral density contrast as a function of depth. It was further estimated the contribution of the GPE and the lithospheric deviatoric stress field for Indo-Eurasia collision zone and executed a qualitative comparison of these reckoned deviatoric stresses with the GPS velocity derived strain rate field and seismo-tectonic stress. Such a comparison shows that, the deviatoric stress field generated by the buoyancy sources within the lithosphere is able to provide a good match to the strain rate observation and seismo-tectonics stress in the study region i.e. Indo-Eurasian collision zone and Shillong plateau region. In Indo-Eurasian collision zone, the high compressive deviatoric stress field arising north of Indo-Gangetic Plains (IGP) along the Himalayan arc seems to be associated with crustal heterogeneities. The small scale clusters of moderately high stress gradients seem to be positionally correlated with the regions where the ridges such as the Delhi Hardwar Ridge (DHR) and Faizabad Ridge (FZR) and Monghyr-Saharsa Ridge (MSR) transgress transversely the Himalayan arc. The seismo-tectonic of the Indo-Eurasian collision zone is 105 also influenced by crustal flow peripheral to EHS region. Such crustal flows are authentically delineated by Magneto-Telluric (MT) studies. The integrated study of deviatoric stress governing seismo-tectonic stress coupled with GPS derived strain rate allows us to infer that the total stress field around the EHS, which can broadly be viewed as a localized ductile flow at mid-crustal depth superposed on the topographically induced deviatoric stress field. This is also found in the case of the Indo-Eurasian collision zone, the ridge-push force, which has been invoked as the sole mechanism behind the present stability of the Tibetan Plateau. This force is unable to cancel out the large deviatoric N-S tension at the Tibetan Plateau that is generated from deviatoric stress due to high GPE. In the Shillong Plateau region, the stress tensor inversion from focal mechanism solution yields consistent results with the deviatoric stress associated from GPE. It is observed that the western part of the plateau has a NNW compression while the eastern part possesses NNE compression. GPE associated deviatoric stress has also brought clear picture on the stress field of the Shillong plateau, which is found to vary from its western edge to eastern edge due to higher topography and density heterogeneities. After examining the first and second order stress contributors in this region, it is also ascertained that the Himalayan back thrust and GPE stresses collectively govern the stress pattern in the Shillong plateau region. Understanding GPE derived deviatoric stresses in Indo-Eurasian collision zone is vital in assessing the stress distribution and occurrence probability of the large earthquakes in these critically stressed regions. Away from the Himalaya, in Indonesia and Japan subduction region, following major earthquakes, the Coulomb stress changes, persisting transient stresses, spatio-temporal seismic pattern in turn hasten/retard the impending earthquake at critically stressed faults and thus increasing the level of seismic risk in 106 subduction zones such as the eastern coast of northern Japan and Indonesia region. Nevertheless, the co and postseismic viscoelastic relaxation processes have far reaching consequences in influencing the impending earthquakes in the Himalaya region as well. It is enigmatic that the tectonic forces cause the earthquakes and occurrence of these earthquakes in different tectonic scenarios in turn provides understanding on first and second order tectonic forces. The stress in the lithosphere also plays an important role in understanding various geophysical events such as plate driving mechanism, energy budget of the earth and earthquake mechanism. The accumulated stress not only gets released by earthquake process but also gets redistributed. Pertaining to this aspect, I have studied coseismic and postseismic deformation processes following the Indian Ocean and TohokuOki earthquakes as these studies provide stress perturbations and their manifestations on aftershocks activity and subsequent earthquakes. The coseismic deformation and Coulomb stress changes have been studied for the Indian Ocean doublet earthquake possessing almost the same moment magnitude Mw 8.6 and 8.2 respectively. Due to these earthquakes the Coulomb stress has increased by ~ 0.5 MPa and decreased by ~ 0.4 MPa. In the Indian Ocean earthquake region, three clusters of aftershocks have been observed, in which two of them occurring within the rupture zone and third one away from the rupture. It is surmised that two aftershock clusters observed in earthquake ruptured zone may be due to the response of relatively large Coulomb stress change, while another cluster away from the rupture is probably due to remotely triggered events, which may occur in the weak zone or already stressed zone. The seismic waves from a large distant earthquake is capable of changing the conductivity and pore fluid pressure in the earth’s crust, which in turn perturb hydrothermal system and redistribute pore pressure. The increased seismic activity is governed by hydro-thermal coupling linked to the above 107 mentioned poroelastic effects. Such triggered events are generally characterized by a relatively small magnitude. In case of the Tohoku-Oki earthquake, there is a notable clustering of aftershocks near the edges of the main rupture suggesting that these events are triggered by the redistribution of stress following the mainshock. The study of the aftershock events showed that 60 % of all events have occurred in Coulomb stress increased region. It is important to affirm that Coulomb stress changes caused the aftershocks. At the northern end it is not clear that the portion of the fault is freely slipping without generating earthquakes or locked and building up strain to cause another earthquake. On the other hand at the southern end, the increase in the Coulomb stress either hastens slow slip events if the region is conducive for such silent earthquakes or decreases the seismic risk; else under the circumstances of no slipping leading to another earthquake e.g. Nias earthquake occurred in 2005 following the 2004 Sumatra earthquake. Following an earthquake the postseismic relaxation takes place by various relaxation mechanisms such as afterslip below the seismic rupture, viscoelastic relaxation in the upper mantle and poroelastic relaxation close to the rupture zone etc. most likely concurrently taking place, each process with its own distinct spatio-temporal characteristics. For nearfield as well as for far-field, the direction of all postseismic displacement vectors is similar to that of the coseismic offsets. Such postseismic deformation suggests that the stress relaxation is taking place by afterslip mechanism which is quite common for large earthquakes in subduction zones. My studies pertaining to crustal deformation due to ambient or/and monotonically varying lithospheric stress caused by various tectonic driving forces with geological time scales in the back drop of stress perturbations caused by intermittent co and postseismic 108 phases of earthquakes from the GPS measurement helped in advancement of knowledge with following main implications; (i) The topographic related stress is imperative in evaluating the probability of the earthquake occurrences in the critically stressed regions (ii) superposed on the Coulomb stress change, the spatio-temporal transient stress may promote the occurrence of the subsequent earthquakes and increase the seismic hazard in the region. For the quantitative estimations of regional and local tectonic stress fields and deformation in the crust, numerical method is a very powerful tool, which permits the modeling of the various structures and deformation on full scale and is able to compute stress/strain values over a long period of time, using various constitutive laws pertaining to rheology. The numerical simulations are finally compared with the recorded microseismicity, focal mechanism solutions, active faulting and GPS measurement in the seismic active region which can provide a better understanding of the present-day regional stress field.
A Thesis submitted to the University of Mumbai for the Ph.D., in Physics under the guidance of Prof. C.D. Reddy
Keywords: PhD Thesis; Crustal deforrmation; GNSS Techniques; Lithospheric stress; Ocean; Earthquake; Tohoku-Oki earthquakes